Kondisi Sosial Ekonomi Petani Padi Di Kecamatan Kota Utara Kota Gorontalo (Studi Kasus : Kelurahan Wongkaditi Barat dan Kelurahan Dulomo Utara) - Bau, Jihan Siti Fadila; Rusiyah, Rusiyah; Kobi, Wiwin (-, 2025)
Kota Utara Subdistrict is the largest rice-producing area in Gorontalo City, particularly in Wongkaditi Barat and Dulomo Utara Subdistricts. However, farmers in this area face various socio-economic challenges that result in incomes that do not match their expenditures. This research adopts a descriptive qualitative approach to examine the socioeconomic situation of farmers along with the elements that affect it Information was gathered via observation, interviews, and surveys from 60 farmers, then analyzed descriptively and spatially using ArcGIS tools. The results show that most farmers are of productive age, have low educational backgrounds, few dependents (husband, a wife, and no more than three children), and live in their own concrete houses. Economically, they cultivate small plots of land, have limited capital, and face high production costs, resulting in seasonal incomes generally below IDR 5,000,000. The sharecropping system further limits their earnings. Policy interventions such as capital assistance, access to agricultural technology, and stabilization of crop prices are needed.